Evaluation of the addresses of public centers in Euskadi - Ayarza Elorriaga, Sira (Avances en Supervisión Educativa, 2018)
This article analyses the evaluation of the school managements of the publicly owned centres that agree to direct them for a period of 4 years with a Management Project. The objective is to have a stable management that lead the Basque public schools through strategic projects, which in the light of educational research and practice, is essential in the required processes of change and transformation to provide a quality educational response to the students, and with it help them reach school success.The role of the Education Inspectorate in this process is described, performing functions of accompaniment, reflection and contrast; issuing reports with proposals for improvement and creating mutual bonds of trust that generate interpersonal relationships facilitating advances in improvement.It ends with conclusions that provide an optimistic view of the process, despite its complexity.
Keywords: school management; pedagogical leadership; evaluation; dimensions; criteria; improvement; Inspection